Virucidal Activity of the Pyridobenzothiazolone Derivative HeE1-17Y against Enveloped RNA Viruses - Rafaela Milan Bonotto; Francesco Bonì; Mario Milani; Antonio Chaves-Sanjuan; Silvia Franze; Francesca Selmin; Tommaso Felicetti; Martino Bolognesi; Soultana Konstantinidou; Monica Poggianella; Chantal L. Márquez; Federica Dattola; et al. (Viruses, 2022)
Pyridobenzothiazolone derivatives are a promising class of broad-spectrum antivirals. However, the mode of action of these compounds remains poorly understood. The HeE1-17Y derivative has already been shown to be a potent compound against a variety of flaviviruses of global relevance. In this work, the mode of action of HeE1-17Y has been studied for West Nile virus taking advantage of reporter replication particles (RRPs). Viral infectivity was drastically reduced by incubating the compound with the virus before infection, thus suggesting a direct interaction with the viral particles. Indeed, RRPs incubated with the inhibitor appeared to be severely compromised in electron microscopy analysis. HeE1-17Y is active against other enveloped viruses, including SARS-CoV-2, but not against two non-enveloped viruses, suggesting a virucidal mechanism that involves the alteration of the viral membrane.